The Effect of Teacher Pedagogic Competence and Discipline on the Performance of Elementary School Teachers during the Covid-19 Pandemic - Muslih Muslih; RM. Teguh Supriyanto; Maximus Gorky Sembiring (research, training and philanthropy institution Natural Aceh, 2023)
The focus of this research is the effect of teacher pedagogic competence and discipline on teacher performance in Kunduran District, Blora Regency. Teacher performance can be seen from their work performance in managing learning activities. This study used a sample of 172 respondents. Three variables are examined in this study: academic competence, discipline, and teacher performance. The data collection method that researchers use is a questionnaire. Methods of data analysis using SPSS Statistics 20 and Excel Office 2010 software. Based on the research and followed by data analysis using multiple linear regression, shows 1) teacher performance influences pedagogical competence; 2) teacher performance is influenced by teacher discipline; 3) and teacher performance can influence pedagogical competence and discipline together. multiple regression equation Y = 33.304 + 0.132X ₁ + 0.304X ₂ + e. This study's results mean that teachers with high work motivation and high work discipline can provide the best performance results to improve the quality of learning.